Cuidando da criança desnutrida no contexto de sobrevivência e resistência - Lopes, Maria do Socorro Vieira (2001)
The infantile malnutrition is considered one of the most important problems of mundial colective health, specially in the developed countries. It is in the fase of alimentar transition from the 6° month, that the child find more vulnerability. In this fase of life, the care done to the child want to garantee her survived, growing and health developed, being this influenced by differents cultures, and even by groups of a same culture. This study had the aims: to understand the practices of care to the undernourished child by the mother or by who take care of the child at home, for identify the factors that contribute for the lost pound; to know the mother perception about the child lost pound; to know the undernourished child care way at home and to interpret the culture determinants of the mother in this care way. Using the ethnonursing, as a study line and the Culture Care Diversity and Universality Theory (Leininger, 1991), as a theoric and methodologic referencial in the collect and analise of the dates. The instruments used in the camp fase were: participant observation and open interview. The scenery was the Nutrition Center of Conjunto Palmeiras, in Fortaleza- Ceará-Brazil and the houses of the undernourished children from april to september,2000. The informants were the carers mothers. The results shows that the care practices done by the mother with the undrenourished child are influenced by some factors: economic, social, educational, way of life. Each care practice done by the mothers shows meanings diversity, each mother has her own care way depending of her recourse. The children lost pound is given for macrostructures reasons like: unemployment, lack of sanitation and water access. In this way, the culture care focus aim an holistic attendance, that search the involvement with the others societal segments, seen that these mothers take care of their children in a survival and resistence context, they do not want that their children lost pound, but in many circumstance, alone they do not get avoid.